The Influence of Organizational Culture and Compensation on Employee Performance (Study on Employees of Grogol Branch Pawnshop) - Supriyanto Supriyanto; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Dinasti International Journal of Management Science, 2023)
Organizational culture is one way of company management to be able to make changes by strengthening the external and internal sides of the company and compensation is direct goods or indirect goods obtained by employees in return for services rendered to the company a leader in terms of fundamentally behaving differently when leading can have an impact on employee performance. This matter needs to be considered by the company because organizational culture and compensation will be able to realize the performance of its employees so that the company's pace can run optimally. The objectives to be achieved in the study are: Do Organizational Culture and Compensation simultaneously affect Employee Performance at Grogol Branch Pawnshop. Multiple linear regression analysis techniques. The study used primary data obtained by filling out a questionnaire and statistical processing using the SPSS 24 program. The results of the research on organizational culture have no effect on the performance of employees of the Grogol Branch Pawnshop. The relationship between organizational culture and employee performance is stated to be low and the magnitude of the influence of organizational culture on employee performance is 0.21%, Compensation affects employee performance, the correlation relationship between compensation and employee performance is low and the magnitude of the influence of compensation on employee performance is 13.5%, Organizational culture and compensation simultaneously have no influence and are significant to the performance of individual employees at Grogol Branch Pawnshop. The magnitude of the relationship between organizational culture and compensation with employee performance simultaneously is moderate, and the magnitude of the influence is 14.2%. Conclusion There is an organizational culture (X1), compensation (X2) has a simultaneous effect on employee performance (Y), meaning that if the organizational culture and compensation are increased, employee performance will be higher. Organizational culture and compensation simultaneously have no significant effect on employee performance. This can be shown from the amount of Fcount smaller than Ftable (2,226 < 4,210).